Implementasi Metode Iqro′ dalam Peningkatan Kemampuan Membaca Santri TPQ As-Salam Desa Bejiruyung - Luthfiyyah, Hilmi Wafa'; Hasanah, Nginayatul (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
Al-Qur'an contains all the rules and all aspects of human life. The obligation to learn the Qur'an is the right of every human being to introduce the Qur'an from an early age, as the main step by introducing hijaiyah letters, learning to pronounce according to the makhorijul letters clearly and correctly. Therefore it takes the right method, one of which is the Iqro' method. This study aims to examine: (1) Implementation of the Iqro′ method in the TPQ As-Salam of Bejiruyung Sempor Village, Kebumen, (2) Supporting and inhibiting factors for the implementation of the Iqro′ method in the learning process of the Qur'an for students of TPQ As-Salam in Bejiruyung Sempor Village Kebumen. The author conducted research using a descriptive qualitative approach, so that the research results obtained were in the form of descriptive data. Data collection by way of observation, interviews and documentation. Then data reduction, presented and conclusions drawn from the data obtained. The results of the study concluded that the Iqro′ method was very supportive and effective in the process of increasing the ability to read the Koran for the students of the AL-Quran As-Salam Education Park according to the rules of recitation. Supporting and inhibiting factors: (a) Supporting factors, the enthusiasm of the students to learn is high, the presence of assistant teachers, the ability of skilled ustadz/ustadzah and the support of the santri guardians. (b) Inhibiting factors, the different characters of the students, the attitudes and actions of the students who were not good, and the inadequate Iqro'.